ROENTGENO-MORFOLOGICAL PECULIARITIES OF CHANGES AT PULPITS THAT АCCOMPАNIED BY FORMATION IN THE PULP LITTLE MINERALIZED METAPLASTIC BONE TISSUE - Yugov, V.K.; Skripnikova, T.P.; Bubliy, T.D. (World of Medicine and Biology, 2012)
Radiological manifestations at pulpitis may be in the form of parts of darkening on the background of less dense tissues deposit of substitutional dentine in the form of denticles or petrification both in the center and at the wall or decreasing of dimension and deformations of the tooth cavities on the account of deposits of substitutional dentine on the walls of tooth cavities. Observed the thickening of the root in the account of hypercementosis.